2015
DOI: 10.1155/2015/736826
|View full text |Cite
|
Sign up to set email alerts
|

Increase in the Tibial Slope Reduces Wear after Medial Unicompartmental Fixed-Bearing Arthroplasty of the Knee

Abstract: Introduction. Unicompartmental arthroplasty of the knee in patients with isolated medial osteoarthritis gives good results, but survival is inferior to that of total knee prosthesis. Knees may fail because positioning of the prosthesis has been suboptimal. The aim of this study was to investigate the influence of the tibial slope on the rate of wear of a medial fixed-bearing unicompartmental knee arthroplasty. Materials and Methods. We simulated wear on a medial fixed-bearing unicompartmental knee prosthesis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…50 In addition, the AP kinematics and IE rotation varied in a range of a few millimetres and a few degrees. 51,52 In general, we believe that low contact stress produced low wear. Therefore, increased congruency is preferable in a joint arthroplasty design since it leads to low contact stress owing to a high-contact area.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…50 In addition, the AP kinematics and IE rotation varied in a range of a few millimetres and a few degrees. 51,52 In general, we believe that low contact stress produced low wear. Therefore, increased congruency is preferable in a joint arthroplasty design since it leads to low contact stress owing to a high-contact area.…”
Section: Discussionmentioning
confidence: 88%
“…This is because C-UKA showed limited AP and IE kinematics compared with conventional UKA in knee simulator studies. 51,52,59 UKA performance can be evaluated through different criteria including kinematics, contact mechanics, and functional outcome tribological behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Knee wear simulator and finite element studies demonstrate increased wear with: joint line deviation, 91 ACL transection, 78 , 92 and limited tibial slope. 93 , 94 In addition, many studies hypothesize substantial effect of debris (e.g. cement) on wear.…”
Section: Resultsmentioning
confidence: 99%
“…Weber et al 19 reported that certain increase of the tibial slope angle will reduce the abrasion of the implant, and by matching the alignment correctly complication such as implant failure can be reduced.…”
Section: Discussionmentioning
confidence: 99%